1996
DOI: 10.1111/1523-1747.ep12329912
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Administered Psoriasis Area and Severity Index Is Valid and Reliable

Abstract: The self-administered psoriasis area and severity index (SAPASI) is a structured instrument for measuring the severity of psoriasis. This study examines the validity, reliability, and responsiveness of the SAPASI. Trained personnel performed a psoriasis area and severity index (PASI) assessment on the same day a SAPASI was obtained from 80 subjects. The validity of the SAPASI was demonstrated using the PASI as the standard (r2 = 0.59, p = 0.0001). Significant correlations were found between SAPASI and PASI for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
233
3
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(249 citation statements)
references
References 12 publications
7
233
3
6
Order By: Relevance
“…The Psoriasis Area and Severity Index (PASI; Feldman et al 233 ) is an internationally accepted, clinician-rated, psoriasis-specific score, based on the body surface area involved and on semi-quantitative estimation of erythema, infiltration and scaling; it is by far the most common tool in clinical studies and in daily practice. The head, trunk, and upper and lower extremities are assessed Scores range from 0 (no psoriasis) to 72 (extremely severe psoriasis)…”
Section: Pasimentioning
confidence: 99%
“…The Psoriasis Area and Severity Index (PASI; Feldman et al 233 ) is an internationally accepted, clinician-rated, psoriasis-specific score, based on the body surface area involved and on semi-quantitative estimation of erythema, infiltration and scaling; it is by far the most common tool in clinical studies and in daily practice. The head, trunk, and upper and lower extremities are assessed Scores range from 0 (no psoriasis) to 72 (extremely severe psoriasis)…”
Section: Pasimentioning
confidence: 99%
“…It can be reliably performed by dermatologists and clinicians from other specialties after short training [15,16]. The selfadministered version of PASI (SAPSI) that is performed by psoriasis patients correlates well with PASI [17]. One of the important qualities of PASI is its responsiveness to change, which is very important in clinical drug trials [17,18].…”
Section: Assessment Of the Skinmentioning
confidence: 99%
“…The selfadministered version of PASI (SAPSI) that is performed by psoriasis patients correlates well with PASI [17]. One of the important qualities of PASI is its responsiveness to change, which is very important in clinical drug trials [17,18]. A recently published systematic review that compared several clinical tools for assessment of psoriasis severity concluded that PASI was the most valid and reproducible clinical severity score in the management of patients with plaque psoriasis [19•].…”
Section: Assessment Of the Skinmentioning
confidence: 99%
“…There are separate distinct patient-reported psoriasis outcome measures: Self-Administered PASI (SAPASI), Visual Analog Scale (VAS), and Psoriasis Symptoms Inventory (PSI) [13][14][15][16][17]. Attempts to incorporate both the physician's and patient's assessments have led to the creation of composite severity scales, such as the National Psoriasis Foundation Score (NPF-PS), Salford Psoriasis Index (SPI), and Dermatology Index of Disease Severity (DIDS), all of which are not commonly utilized [18][19][20][21][22].…”
Section: Existing Psoriasis and Psoriatic Arthritis Outcome Measuresmentioning
confidence: 99%